To Serve and Protect Whom? Using Composite Counter-Storytelling to Explore Black and Indigenous Youth Experiences and Perceptions of the Police in Canada - Samuels-Wortley, Kanika (Crime & delinquency, 2021)
Research based in the US and Britain have established that perceptions of the police are particularly low among youth and racialized communities. However, by contrast, little is known about racialized youth perceptions of the police within Canada. Due to formal and informal bans on the collection of race-based data, Canada maintains its international reputation as a tolerant multicultural society. Using the critical race methodology of composite counter-storytelling, this paper will highlight the perspectives of Black and Indigenous youth and explore their experiences with law enforcement. This aims to counter Canada’s international status as a multicultural utopia and demonstrate how legal criminal justice actors, such as the police, perpetuate the marginalized status of Black and Indigenous youth through the process of criminalization.